Tailored Morphology and Phase Evolution of Magnesium Whitlockite Granules via a Dissolution–Precipitation Approach - Ruta Raiseliene; Greta Linkaite; Akvile Ezerskyte; Inga Grigoraviciute (Applied Sciences, 2025)
Magnesium whitlockite (Mg-WH) has emerged as a promising biomaterial for bone regeneration due to its compositional similarity to natural bone minerals. This study aimed to systematically modify a dissolution–precipitation synthesis method to produce Mg-WH granules with tailored morphologies and controlled phase compositions for possible use in bone regeneration applications. Three distinct precursor granules were prepared by mixing varying amounts of ammonium dihydrogen phosphate and magnesium hydrogen phosphate with calcium sulfate. The precursors were then transformed into biphasic and single-phase Mg-WH granules by means of immersion in magnesium- and phosphate-containing solutions under controlled conditions. The X-ray diffraction results demonstrated that biphasic materials containing Mg-WH and either calcium-deficient hydroxyapatite (CDHA) or dicalcium phosphate anhydrous (DCPA) formed after 24 h of synthesis, depending on the synthesis conditions. Prolonging the reaction time to 48 h resulted in complete transformation into single-phase Mg-WH granules. Fourier-transform infrared spectroscopy confirmed the presence of functional groups characteristic of Mg-WH, CDHA, and DCPA in the intermediate products. The spectra also indicated the absence of precursor phases and the progressive elimination of secondary phases as the reaction time increased. Scanning electron microscopy analyses revealed notable morphological transformations from the raw granules to the product granules, with the latter exhibiting interlocked spherical and rod-like particles composed of fine Mg-WH rhombohedral crystals. N2 adsorption–desorption analyses exposed significant differences in the surface properties of the synthesized granules. By varying precursor, reaction solution compositions, and reaction times, the study elucidated the phase evolution mechanisms and demonstrated their impact on the structural, morphological, and surface properties of Mg-WH granules.